Empowering Teachers? An Exploratory Study of Personnel Practices in Virtual Charter Schools in the United States - Dennis Beck; Robert Maranto (Flexible Learning Association of New Zealand, 2014)
Virtual charter schools have the potential to transform teacher personnel management. However, there is currently little evidence that they are doing so. This study examined how 89 teachers at two virtual charter schools perceived school personnel practices and leadership. Survey analysis indicated that teachers perceived personnel practices as resembling those of their previous 'brick and mortar' public schools. The results also showed that these teachers had a more positive view of school leaders and the school climate than they had at their previous schools. Implications are discussed in light of teacher education and personnel management literature. Additional research is recommended, as is development of the preparation of school administrators to include online, flexible, and distance learning, and related innovative leadership practices.